2015
DOI: 10.1088/0004-637x/806/2/159
|View full text |Cite
|
Sign up to set email alerts
|

Neutrino and Cosmic-Ray Emission and Cumulative Background From Radiatively Inefficient Accretion Flows in Low-Luminosity Active Galactic Nuclei

Abstract: We study high-energy neutrino and cosmic-ray (CR) emission from the cores of low-luminosity active galactic nuclei (LLAGN). In LLAGN, the thermalization of particles is expected to be incomplete in radiatively inefficient accretion flows (RIAFs), allowing the existence of non-thermal particles. In this work, assuming stochastic particle acceleration due to turbulence in RIAFs, we solve the Fokker-Planck equation and calculate spectra of escaping neutrinos and CRs. The RIAF in LLAGN can emit CR protons with 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
173
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(187 citation statements)
references
References 101 publications
6
173
0
8
Order By: Relevance
“…The CRs are likely to exist inside accretion flows when the mass accretion rate is sufficiently lower than the Eddington rate (e.g., Kimura et al 2014). The existence of CRs is expected from the theoretical estimate (e.g., Kimura et al 2015), numerical simulations (e.g., Hoshino 2015), and modeling of the observed photon spectra (e.g., Nemmen et al 2014), although gamma rays from accretion flows have not yet been detected (Wojaczynski et al 2015).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The CRs are likely to exist inside accretion flows when the mass accretion rate is sufficiently lower than the Eddington rate (e.g., Kimura et al 2014). The existence of CRs is expected from the theoretical estimate (e.g., Kimura et al 2015), numerical simulations (e.g., Hoshino 2015), and modeling of the observed photon spectra (e.g., Nemmen et al 2014), although gamma rays from accretion flows have not yet been detected (Wojaczynski et al 2015).…”
Section: Discussionmentioning
confidence: 97%
“…This process has been analytically formulated using the quasi-linear theory, and the evolution of the momentum distribution function of the CRs has usually been described by the diffusion equation in momentum space (e.g., Schlickeiser & Miller 1998;Stawarz & Petrosian 2008;Ohira 2013). Kimura et al (2015) investigate stochastic acceleration inside RIAFs of low-luminosity active galactic nuclei by using this formulation, and they find that CRs can be accelerated up to ∼10 PeV if the turbulence is on the Kolmogorov spectrum and that high-energy neutrinos generated through the interaction between CRs and background matter are compatible with the IceCube events (Aartsen et al 2013(Aartsen et al , 2015. Protons escaping from RIAFs interact with circumnuclear matter and emit gamma rays (Fujita et al 2015), which can be consistent with the observed TeV flux from Sgr A * (Aharonian et al 2009b) and Cen A (Aharonian et al 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Many papers discuss the neutrino emission from one specific source class by adopting a modeldependent approach, for active galactic nuclei (AGNs) [9][10][11][12][13][14][15][16][17][18], star-forming galaxies [19][20][21][22][23][24][25][26][27][28], gamma-ray bursts [29][30][31][32][33][34][35][36], galaxy clusters [37][38][39][40], and dark matter decays [41][42][43][44][45].…”
Section: Tomographic Constraints On High-energy Neutrinos Of Hadronucmentioning
confidence: 99%
“…For instance, Waxman and Bahcall(1999) predicted a cosmic neutrino flux proportional to E −2.0 , according to the standard Fermi acceleration mechanism at shock fronts (Fermi 1949 g have suggested the presence of an additional component dominating at lower energies (E ν 200 TeV), on top of a single unbroken power-law flux (see Chen et al 2015;Vincent et al 2016;Anchordoqui et al 2017;see Kopper 2016 for studies of a neutrino flux with two power-laws and Kimura et al 2015;Murase et al 2016;Senno et al 2016 for viable hidden astrophysical candidates). The two-component scenario is also strongly motivated by the analyses performed on the up-going muon neutrinos (Aartsen et al 2016).…”
Section: Introductionmentioning
confidence: 99%